2022
DOI: 10.1021/jacs.2c10545
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Chemical Activation of Enzyme-Inducible CRISPR/Cas9 for Cell-Selective Genome Editing

Abstract: The precision and therapeutic potential of CRISPR/Cas9 genome editing are greatly challenged by the less control over Cas9-mediated DNA cleavage. Herein, we introduce a conditional and cell-selective genome editing system controlled by disease-associated enzymes, termed enzyme-inducible CRISPR (eiCRISPR). eiCRISPR comprises Cas9 protein, a self-blocked inactive single-guide RNA (bsgRNA), and a chemically caged deoxyribozyme (DNAzyme) that activates bsgRNA and eiCRISPR in a controllable manner. We design chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…Moreover, Cai et al successfully demonstrated a spatiotemporally controllable cell-selective genome editing technique using biodegradable lipid-based LNP (Figure 13f). [317] The genome editing system is regulated by enzyme-inducible CRISPR/Cas9 (eiCRISPR) comprising of Cas9 protein, self-blocked inactive single-guide RNA (bsgRNA), and deoxyribozyme (DNAzyme). DNAzyme could be activated by upregulated NAD(P)H:quinone oxidoreductase (NQO1) signals in the disease cells, which cleaves the blocking region of bsgRNA, and further activates eiCRISPR for tumor cell-selective genome editing.…”
Section: Gene Therapymentioning
confidence: 99%
“…Moreover, Cai et al successfully demonstrated a spatiotemporally controllable cell-selective genome editing technique using biodegradable lipid-based LNP (Figure 13f). [317] The genome editing system is regulated by enzyme-inducible CRISPR/Cas9 (eiCRISPR) comprising of Cas9 protein, self-blocked inactive single-guide RNA (bsgRNA), and deoxyribozyme (DNAzyme). DNAzyme could be activated by upregulated NAD(P)H:quinone oxidoreductase (NQO1) signals in the disease cells, which cleaves the blocking region of bsgRNA, and further activates eiCRISPR for tumor cell-selective genome editing.…”
Section: Gene Therapymentioning
confidence: 99%
“…This strategy reduces the negative effects of genome editing technology and improves the therapeutic potential of genome editing technology (Figure 6). [11] …”
Section: Intracellular Delivery Of Crispr Mrna For Cell‐selective Gen...mentioning
confidence: 99%
“…[6] Therefore, mRNA holds great promise for developing biotherapeutics for treating a large variety of genetic disorders, including protein replacement therapy, [7] mRNA vaccines, [8,9] immunotherapies, [10] and gene editing. [11] mRNA is a large, negatively charged biomacromolecule that faces significant challenges in attempting to penetrate cell membranes spontaneously. In addition, mRNA is prone to rapid degradation in various biological settings, such as blood and other body fluids.…”
Section: Introductionmentioning
confidence: 99%
“…6 For example, clustered regularly interspaced short palindromic repeatsassociated protein 9 (CRISPR-Cas9) technology has been found to reverse MDR mediated by ATP-binding cassette (ABC) transporters with a significantly higher outcome than other gene editing technologies due to its simple design, flexible target region, higher editing efficiency and multiplexing. [7][8][9][10] Despite great advances, the majority of CRISPR-Cas9 systems still suffer from some formidable problems, including off-target genomic alterations and genotoxicity, potential immunological risk by Cas9-specific T-cells, and unsatisfactory targeted delivery. 8 To address this challenge, CRISPR-Cas13d, a RNAguided Type VI Cas protein, has been identified for target gene knockdown without altering the genome.…”
Section: Introductionmentioning
confidence: 99%